Infestation of royal python (python regius) with ticks amblyomma hebraeum in Ibadan Zoo, Nigeria (2003)
Tick infestation in royal python is reported. Clinical signs included dullness and inactivity evident in reaction to its prey. Parasitological examination revealed Amblyomma hebraeum. Epidemiological investigation showed WAD goat with external parasite within the reptile area.